THE IMPORTANCE OF TECHNOLOGIES OF PRESERVATION AND RESTORATION OF HISTORICAL SETTLEMENTS - Khurramov Ikrom Kholmuradovich (Journal of new century innovations, 2022)
In this article, the factors that cause the disappearance of historical and cultural monuments and the legal documents accepted at the international level are analyzed, and the possibilities of using modern technologies for the restoration of historical monuments and the use of these technologies in our country are studied.